2018
DOI: 10.1016/j.envint.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transport mode use on self-perceived health, mental health, and social contact measures: A cross-sectional and longitudinal study

Abstract: Similarity of findings across cities suggested that active transport, especially bicycle use, should be encouraged to improve population health and social outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 43 publications
(57 reference statements)
3
44
0
3
Order By: Relevance
“…Encouraging active commuting is one of the most important agendas in the fields of urban planning and design, transportation planning and engineering, environmental planning, and even public health. Several studies have identified individual health benefits of active commuting [5][6][7][8][9][10][11][12][13][14][15], and a report from Public Health England also identified its benefits for the wider population including reductions in air pollution, noise, and economic costs [79]. Thus, efforts are being made by policymakers from a multitude of countries to change citizens' commuting behaviors toward active commuting, and Seoul is no exception [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Encouraging active commuting is one of the most important agendas in the fields of urban planning and design, transportation planning and engineering, environmental planning, and even public health. Several studies have identified individual health benefits of active commuting [5][6][7][8][9][10][11][12][13][14][15], and a report from Public Health England also identified its benefits for the wider population including reductions in air pollution, noise, and economic costs [79]. Thus, efforts are being made by policymakers from a multitude of countries to change citizens' commuting behaviors toward active commuting, and Seoul is no exception [20].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced car use due to active commuting can lead to a decrease in air pollution and traffic congestion, and more efficient use of urban land due to a reduction in parking lots [2][3][4]. Moreover, active commuting has several health benefits, including increasing physical activity [5] and promoting mental health [6][7][8], and reducing obesity [9], cardiovascular diseases [10][11][12], type 2 diabetes [13], cancers [10,12], and all-cause mortality [10,14,15]. Avila-Palencia et al have examined the relationship between bicycle commuters and perceived stress in Barcelona, Spain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor energy efficiency in housing is having a direct effect on the physical health of UK residents. In the winter period between 2016 and 2017, there were an estimated 34 300 excess winter deaths in the UK, 20 of which approximately a third were estimated to be attributable to living in a cold home. Excess winter deaths were three times higher in the coldest quarter of homes than in the warmest quarter.…”
Section: Health and The Nhsmentioning
confidence: 99%
“…It is important to mention that promoting active modes of transport has a plethora of co-benefits that help cities achieve other health and environmental objectives beyond overweight/obesity levels. The health benefits of physical activity go beyond weight loss, with conclusive literature showing the benefits of active transport associated with mental health (Avila-Palencia et al 2018;Mueller et al 2015) and significant levels of reduction in all-cause mortality (Mueller et al 2018). When an increase in bicycling and walking is promoted as modal shift from personal motorized transport, these changes also imply reductions in both greenhouse gas and local pollutant emissions (Xia et al 2013).…”
Section: Links Between Active Transport and Overweight/ Obesitymentioning
confidence: 99%